Pengaruh Penambahan Limbah Bulu Ayam Terhadap Kuat Tekan Beton K-250 - Rokhim, Muhammad; Dhana, Rio Rahma (Universitas Batanghari Jambi, 2024)
Along with the times, various innovations have been made to improve the performance of concrete, Innovations carried out include aiming to produce and value structural materials that have good properties with economical and economical methods and costs, Efforts to improve the quality of concrete are also carried out by mixing other ingredients in the mixture. In this study, the author used chicken feather fiber as an added ingredient to the mixture concrete. This study aims to find out how the process of making concrete with added chicken feather waste with an additional composition of 0.1%, 0.5%, and 1.5%, and whether the added material of chicken feather waste with a composition of 0.1%, 0.5%, and 1.5%, can increase the compressive strength of concrete or vice versa. In this research method using the experimental method, the test objects made for each addition to the percentage of chicken feather waste are as many as 3 samples, with a cylindrical mold size of 15 cm in diameter with a height of 30 cm, by passing the treatment process for 28 days. The conclusion of this study is that concrete is added with chicken feather waste with variations of 0.1%, 0.5%, and 1.5% addition, the planned compressive strength is 20.8 Mpa. A decrease in compressive strength was produced in each use of added chicken feather waste with a composition of 0.1%, 0.5%, and 1.5%, the more added chicken feather waste, the compressive strength value of concrete decreased, the initial normal composition produced a compressive strength of 21.56 Mpa, while the composition of 0.1% decreased with a compressive strength result of 10.64 Mpa, then with a composition variation of 0.5% decreased again with a compressive strength value of 3.21 Mpa. And for a composition variation of 1.5% it decreases with a compressive strength value of 0.16 Mpa. With this research, it is known that chicken feather waste material cannot be an alternative to add concrete mixture in the future.